Therapeutic Values of Human Urinary Kallidinogenase on Cerebrovascular Diseases - Wei, Zhenyu; Lyu, Yi; Yang, XiaoLi; Chen, Xin; Zhong, Ping; Wu, Danhong (Frontiers in Neurology, 2018)
The term “tissue kallikrein” is used to describe a group of serine proteases shared considerable sequence homology and colocalize in the same chromosomal locus 19q13.2–q13.4. It has been widely discovered in various tissues and has been proved to be involved in kinds of pathophysiological processes, such as inhibiting oxidative stress, inflammation, apoptosis, fibrosis and promoting angiogenesis and neurogenesis. Human Urinary Kallidinogenase (HUK) extracted from human urine is a member of tissue kallikrein which could convert Kallikrein to kinin and hence improve the plasma kinin level. Medical value of HUK has been widely investigated in China, especially on acute ischemic stroke. In this review, we will summarize the therapeutic values of Human Urinary Kallidinogenase on acute ischemic stroke and its potential mechanisms.